Workload Analysis Using The FT (Full Time Equivalent) Method To Determine The Effective Employee Requirements At Pt. Bank Rakyat Indonesia - Nabil Habieby (Kalam Practica Media, 2026)
Human resources (HR) are a strategic factor that determines the success of an organization in achieving its goals and maintaining performance sustainability, especially in service sectors such as banking. This study aims to analyze employee workload using the Full Time Equivalent (FTE) method to determine the ideal number of employees at PT Bank Rakyat Indonesia. This research uses a descriptive quantitative approach through observation, interviews, and documentation. Workload analysis is conducted by calculating effective working time and work activities in each employee position. The results show that several employee positions experience excessive workload conditions (overload) with FTE values >1.28. Meanwhile, some other employee positions are categorized as normal. This study recommends adding staff to positions with excessive workload to improve work effectiveness and service quality. The implementation of the FTE method has been proven effective in supporting workforce planning decisions objectively and systematically in corporate institutions.